2019
DOI: 10.1177/0265407519860594
|View full text |Cite
|
Sign up to set email alerts
|

Attachment categories or dimensions: The Adult Attachment Scale across three generations in Poland

Abstract: Even though previous attachment taxometric studies supported the conclusion that attachment is rather dimensional than categorical construct, they also did not provide consistent support against categorical approach. Addressing limitations of previous taxometric studies on adult attachment, we asked two research questions: Is attachment as measured by the Adult Attachment Scale (AAS) categorical or dimensional? What is the predictive validity of categorical and dimensional approaches? To answer these questions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…However, some attachment categories are relatively rare; very large samples are required to prevent reducing power. Therefore, the majority of studies within this field report results on secure versus insecure attachment (Lubiewska & van de Vijver, 2013).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…However, some attachment categories are relatively rare; very large samples are required to prevent reducing power. Therefore, the majority of studies within this field report results on secure versus insecure attachment (Lubiewska & van de Vijver, 2013).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In other words, the fit between the categorizations made with similar measurements based on the same model is lower than expected (Sümer, 2006). The findings concerning the relationship between the ECR-RS and categorical models obtained in this study are thought to have stemmed from the fact that these measurement tools are based on different models and that categorical measurements are limited in their capacity to determine individual differences regarding individuals' attachment characteristics (Brennan et al, 1998;Fraley & Waller, 1998;Lubiewska & Van de Vijver, 2020). In order to examine the relationship between attachment characteristics and personality traits according to specific relationships, the relationship between the ECR-RS subscales and SAS subscales was examined.…”
Section: Discussionmentioning
confidence: 88%
“…However, recent studies favor the use of dimensional models to measure individual differences in attachment (Fraley et al, , 2015Fraley, Heffernan, et al, 2011;Fraley & Shaver, 2000;Hudson et al, 2015;Lubiewska & Van de Vijver, 2020). It has been reported that models based on categorical measurements may misrepresent the nature of attachment (Fraley et al, 2015;Fraley & Roisman, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This method examines two categories (patterns) of insecure attachment: attachment anxiety and attachment avoidance. The scale is charactervolume 8(2),  ised by good psychometric properties, including the Polish one (Łubiewska & Van de Vijver, 2014).…”
Section: Methodsmentioning
confidence: 99%